Electrodeposition of gold from formaldehyde-sulfite baths: bath stability and deposits characterization - Juliana L. Cardoso; Sebastião G. dos Santos Filho (Química Nova, 2011)
It was investigated Au(I)-sulfite baths containing formaldehyde. As a result, high stability was achieved for baths containing formaldehyde concentration close to 10 mL L-1 with a lifetime superior to 600 days. On the other hand, cyclic voltammograms indicated that the increase of formaldehyde concentration in the bath promotes decreasing of the maximum cathodic current, so that, if the formaldehyde concentration is high, the surface areal concentration of gold will be low. Also, the lowest surface roughness was obtained for 10 mL L-1 of formaldehyde.